PERAN JALAN PERTANIAN DALAM MENDORONG PERTUMBUHAN EKONOMI PEDESAAN - Maulana Ibrohim Nugraha (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Agricultural roads are one of the infrastructures that play an important role in encouraging the growth and economic development of rural communities, especially in Cimanggu Village, Langkapjaya Village, Lengkong District, Sukabumi Regency. The problem faced by farmers is the limited access to agricultural land in residential areas, which slows down the distribution of harvests and has an impact on the slow turnover of the local economy. This study aims to analyze the contribution of agricultural road development to the economic growth of the community. The methodology used is qualitative, with data collected through literature research, interviews and field observations. The results of the study indicate that agricultural roads play an important role in increasing production efficiency, expanding market access, and creating new jobs in the agricultural transportation sector.